2013
DOI: 10.1371/journal.pone.0077309
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Promoter Methylome of Small Renal Masses

Abstract: The majority of renal cell carcinoma (RCC) is now incidentally detected and presents as small renal masses (SRMs) defined as ≤4 cm in size. SRMs are heterogeneous comprising several histological types of RCC each with different biology and behavior, and benign tumors mainly oncocytoma. The varied prognosis of the different types of renal tumor has implications for management options. A key epigenetic alteration involved in the initiation and progression of cancer is aberrant methylation in the promoter region … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 68 publications
1
17
0
1
Order By: Relevance
“…We chose this cut-off because Illumina has reported that β < 0.15 can be due to the background noise of the assay chemistry at the unmethylated state 15 . In addition, we have found probes with β < 0.15 to typically read as unmethylated (0%) by pyrosequencing of the identical CpG loci 16 . We used the Wilcoxon Rank sum test in a two-group comparison with a P value < 0.05 as significant.…”
Section: Resultsmentioning
confidence: 99%
“…We chose this cut-off because Illumina has reported that β < 0.15 can be due to the background noise of the assay chemistry at the unmethylated state 15 . In addition, we have found probes with β < 0.15 to typically read as unmethylated (0%) by pyrosequencing of the identical CpG loci 16 . We used the Wilcoxon Rank sum test in a two-group comparison with a P value < 0.05 as significant.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, GRIK2 , which is the gene most frequently involved in chromosome 6q deletions in acute lymphocytic leukemia, is regarded as a tumor suppressor gene [ 28 ]. Additionally, hypermethylation of GRIK1 , GRIK2 , GRIN2A and GRIN2B has been reported in ccRCC, gastric cancer, colon cancer, esophageal squamous cell carcinoma and NSCLC [ 29 - 34 ]. Thus, the effect of gain or loss of glutamate receptor function varies in different cancers.…”
Section: Introductionmentioning
confidence: 99%
“…There have been previous reports that have found DNA methylation biomarkers specific for clear cell but provide limited data on other subtypes of RCC and benign tumors [2426]. In our study, we provide detailed methylation profiling of subtypes of benign phenotypes, which we developed from microdissection of FFPE tissue from kidney cases resected at the University of Southern California.…”
Section: Discussionmentioning
confidence: 99%